Difficulties in the Identification of Deep Sea Ophiuroidea Post-Larvae from Makassar Strait, Indonesia and Their Implication for Taxonomic Studies - Supono (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Brittle stars (Ophiuroidea) are one of the most difficult groups to be classified among five classes of echinoderm fauna. This is due to the limited information on their growth and development. Most of information on morphological description and ecology of the identified species were derived from the adult shallow water brittle stars. Meanwhile, the deep sea brittle stars, particularly larval and postlarval stages are less documented due to lack of investigation. This study investigated morphological characteristics of brittle star postlarvae collected from the deep sea of Makassar Strait on 8–15 June 2013. Six individual postlarvae of brittle stars were recorded. The important morphological characteristics of these postlarvae were described as preliminary record for similar future studies. All postlarvae collected in this study demonstrated lack of important structures for identification. Therefore, genetic studies may need to be carried out to identify the samples up to species level.